Effects of treated and untreated loose oil palm fruitlets with pressurized thermal heating on the oxidative state and carotene content in palm oil - Vincent Eddy, Christine Jamie; Shamsudin, Rosnah; Samsu Baharuddin, Azhari (2014)
Carotenoids are fat-soluble microconstituents that are usually found in palm oil and have the capability to exert health beneficial effects in humans, including protection against cancer, cardiovascular diseases, and age-related eye diseases. A comparison of the chemical characteristics of the untreated and the treated loose oil palm fruitlets, with pressurized thermal heating at 98˚C/0.095 MPa, 105˚C/0.121 MPa and 121˚C/0.205 MPa at a period of 4 minutes interval up to 12 minutes, was studied. In addition to higher oil yield, treated loose oil palm fruitlets recorded values for Deterioration rate of Bleachability Index (DOBI) of more than 3 at higher heating temperature and time indicating lower to none oxidation process had occurred due to the decrease in moisture content attained. In relation to this, higher heating temperature and time also indicates higher extraction yield of carotene. However, prolonged heating will make the carotene susceptible to oxidation and degradation occurring from severe processing due to their highly unsaturated nature. Lower to none oxidation state yielded optimal concentration of carotene as antioxidants for the maximal antioxidant activity. Untreated loose fruitlets, on the other hand, recorded lower extraction yield of carotenoids due to the higher moisture content available and higher oxidation state compared to treated fruitlets. The optimum temperature and time needed to produce a high quality palm oil with health-promoting bioactive compounds in terms of the carotene content from the loose fruitlets were attained in this study.